Performance evaluation of reverse logistics in the civil construction sector - Hammes, Gabriela (2021)
Reverse logistics is a logistics activity that prizes for adding value to customers by returning from the consumer product to its origin. This reverse flow, when applied to products at the end of their useful life, makes reverse logistics an environmentally correct measure, since it provides a correct disposal of the waste, which facilitates reuse of material, recycling and remanufacturing, and thus reduces the environmental impact. Due to this, the present article presents a model for evaluating the performance of this important activity in the construction sector - one of the sectors that generates the most waste and which has great economic impact in the country. The construction of this model took three steps: (i) the first one to review the literature to find gaps, define the items to be evaluated, (ii) the second stage was the literature analysis, the creation of the indicators and the confection of the model, (iii) finally, a case study was carried out. The elaborated model deals with internal, external logistics and waste management in order to evaluate the performance of reverse logistics in companies in this sector. The model was applied by means of a case study in a consolidated construction company in the capital of Santa Catarina. In addition, this article points to gaps in future research.